Povezanost između stepena akumulacije toplote u organizmu i pokazatelja termotolerancije i zamora kod toplotnog stresa usled fizičkog napora u uslovima povišene temperature spoljne sredine - Mašić, Siniša T.; Marjanović, Sonja S.; Stojićević, Jelena M.; Jovanović, Vanja M.; Joksimović, Mirjana V.; Ilić, Danijela (Vojnosanitetski pregled, 2022)
Background/Aim. The risk assessment of heat illness and fatigue development is essential in military service. The aim of our study was to investigate the relationship between heat storage and various psychophysiological parameters of heat stress, as well as potential peripheral markers of fatigue in soldiers performing exertional heat stress tests. Methods. Fifteen young, healthy, and unacclimatized men underwent an exertional heat stress test (EHST) with the submaximal workload in warm conditions (WBGT 29 °C) in a climatic chamber. Every 10 min, the following parameters of thermotolerance were measured or calculated: core temperature (Tc), mean skin (Tsk) and body temperature (Tb), heart rate (HR), heat storage (HS), physiological strain index (PSI), as well as peripheral markers of fatigue [blood concentrations of ammonia, urea nitrogen (BUN), lactate dehydrogenase (LDH), cortisol and prolactin] and subjective parameters: thermal sensation (TS) and rate of perceived exertion (RPE). Results. Tolerance time varied from 45 to 75 min (mean 63 ± 7.7 min). Average values of Tc, Tb, and HR constantly increased during EHST, while Tsk reached the plateau after 10 min. Concentrations of all investigated peripheral markers of fatigue were significantly higher after EHST compared to baseline levels (31.47 ± 7.29 vs. 11.8 ± 1.11 µmol/L for ammonia; 5.92 ± 0.73 vs. 4.69 ± 0.74 mmol/L for BUN, 187.27 ±2 8.49 vs.152.7 3± 23.39 U/L for LDH, 743.43 ± 206.19 vs. 558.79 ± 113.34 mmol/L for cortisol, and 418.08 ± 157.14 vs. 138.79 ± 92.83 μIU/mL for prolactin). Conclusions. This study demonstrates the relationship between heat storage and Tc, HR, TS, and RPE, but also with PSI. Concentrations of cortisol and especially prolactin showed a significant correlation with parameters of thermotolerance.